1989
DOI: 10.1128/aac.33.3.382
|View full text |Cite
|
Sign up to set email alerts
|

Effects of beta-lactamases and omp mutation on susceptibility to beta-lactam antibiotics in Escherichia coli

Abstract: omp mutants, MH1160 (MC4100 ompRI) and MH760 (MC4100 ompR2), by transformation. Effects of the combination of the omp mutations and these P-lactamases on the susceptibility of E. coli strains were studied with 15 ,B-lactam antibiotics including cephalosporins, cephamycins, penicillins, imipenem, and aztreonam. The ompRI mutant, MH1160, lacks OmpF and OmpC, and it showed reduced susceptibility to 11 of the 15 P-lactam agents. The reduction in susceptibility to cefoxitin, moxalactam, and flomoxef was much greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 28 publications
3
13
0
Order By: Relevance
“…However, pathogenic bacteria can easily develop high levels of resistance to ␤-lactams by both the loss of porin proteins and the high-level production of ␤-lactamases (6,20). Indeed, Hiraoka et al (25) demonstrated that porin-deficient mutants showed high levels of resistance to ␤-lactams compared with the resistance of the wild-type strain when a large amount of active ␤-lactamase existed in the periplasm. However, the activity of KP-736 was less affected by the combined effect of porin loss and ␤-lactamase production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, pathogenic bacteria can easily develop high levels of resistance to ␤-lactams by both the loss of porin proteins and the high-level production of ␤-lactamases (6,20). Indeed, Hiraoka et al (25) demonstrated that porin-deficient mutants showed high levels of resistance to ␤-lactams compared with the resistance of the wild-type strain when a large amount of active ␤-lactamase existed in the periplasm. However, the activity of KP-736 was less affected by the combined effect of porin loss and ␤-lactamase production.…”
Section: Discussionmentioning
confidence: 99%
“…MH1160 is an ompR1 mutant of MC4100 and lacks the outer membrane proteins OmpF and OmpC (25), while MC4100 has an osmoregulated production of OmpF and OmpC (25). Transformants of MH1160 and MC4100 with pMS510, pMS509, pMS185-2, or pMS182-5 plasmid DNA (25), which contain cloned ␤-lactamase genes of the types penicillinase group 2b (TEM-1) of Rms212 (57), penicillinase (PCase) group 2d (OXA-1) of Rms213 (57), cephalosporinase (CSase) group 1 of Citrobacter freundii GN346 (52), and oxyimino-cephalosporinase (CXase) group 2e of Proteus vulgaris GN7919 (36), respectively, were maintained as stock cultures in our laboratory (25). pMS363 plasmid DNA (30), which contains the cloned ␤-lactamase gene of CXase group 3 of P. aeruginosa GN17203, was provided by S. Iyobe, Gunma University, Gunma, Japan (30).…”
Section: Methodsmentioning
confidence: 99%
“…In this scenario, an alteration in the permeability of the outer membrane to the P-lactam or the inhibitor in the presence of a stable level of ,B-lactamase production would be expected to result in an elevation of the in vitro MIC. Such a phenomenon has been described for E. coli in association with the loss of certain porin proteins (6,19).…”
Section: Discussionmentioning
confidence: 99%
“…The most common mechanism appears to be production of high levels of a 1-lactamase normally susceptible to the inhibitor (10,11,16,20). Increased resistance has also been associated with the loss of expression of certain porin proteins in Escherichia coli (6,19). Other reported mechanisms include the production of a ,B-lactamase normally resistant to the inhibitor, such as the AmpC-type enzymes (3,15), or mutations in a normally inhibited enzyme rendering it resistant to inhibition (3).…”
mentioning
confidence: 99%
“…In Escherichia coli K-12, the major outer membrane porins are OmpF and OmpC. Mutants lacking OmpF porin have increased resistance to 3-lactams, chloramphenicol, quinolones, and tetracyclines (2, 4-6, 8,10,11,18,27). Moreover, in vitro studies using liposomes revealed that the OmpF porin formed much more efficient pores for the diffusion of 1-lactams than OmpC porin (20,21).…”
mentioning
confidence: 99%